The SMILE study: Study of long-term methotrexate and iguratimod combination therapy in early rheumatoid arthritis - Fang Du; Qing Dai; Jialin Teng; Liangjing Lu; Shuang Ye; Ping Ye; Zhiqian Lin; Hong Ding; Min Dai; Chunde Bao; On behalf of the SMILE Group; Xiangxiang Pan (Chinese Medical Journal, 2025)
Abstract. Background:. Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by chronic inflammation and joint destruction. Iguratimod (IGU) is a novel conventional synthetic disease-modifying antirheumatic drugs (csDMARD) with good efficacy and safety for the treatment of active RA in China and Japan. However, the long-term effects of IGU on the progression of bone destruction or radiographic progression in patients with active RA remain unknown. We aimed to investigate the efficacy and safety of iguratimod (IGU), a combination of methotrexate (MTX) and IGU, and IGU in patients with active rheumatoid arthritis (RA) who were naïve to MTX. Methods:. This multicenter, double-blind, randomized, non-inferiority clinical trial was conducted at 28 centers for over 52 weeks in China. In total, 911 patients were randomized (1:1:1) to receive MTX monotherapy (10–15 mg weekly, n = 293), IGU monotherapy (25 mg twice daily, n = 297), or IGU + MTX (10–15 mg weekly for MTX and 25 mg twice daily for IGU, n = 305) for 52 weeks. The patients’ clinical characteristics, Simplified Disease Activity Index (SDAI), Clinical Disease Activity Index (CDAI), disease activity score in 28 joints-C-reactive protein (DAS28-CRP) level, and disease activity score in 28 joints-erythrocyte sedimentation rate (DAS28-ESR) were assessed at baseline. The primary endpoints were the proportion of patients with ≥20% improvement according to the American College of Rheumatology (ACR20) response and changes in the van der Heijde-modified total Sharp score (vdH-mTSS) at week 52. Results:. The proportions of patients achieving an ACR20 response at week 52 were 77.44%, 77.05 %, and 65.87% for IGU monotherapy, IGU + MTX, and MTX monotherapy, respectively. The non-inferiority of IGU monotherapy to MTX monotherapy was established with the ACR20 (11.57%; 95% confidence interval [CI], 4.35–18.79%; P <0.001) and vdH-mTSS (−0.37; 95% CI, −1.22–0.47; P = 0.022). IGU monotherapy was also superior to MTX monotherapy in terms of ACR20 (P = 0.002) but not the vdH-mTSS. The superiority of IGU + MTX over MTX monotherapy was confirmed in terms of the ACR20 (11.18%; 95% CI, 3.99–18.37%; P = 0.003), but not in the vdH-mTSS (−0.68; 95% CI, −1.46–0.11; P = 0.091). However, the difference in the incidence rates of adverse events was not statistically significant. Conclusions:. IGU monotherapy/IGU + MTX showed a more favorable clinical response than did MTX monotherapy. IGU may have some clinical benefits over MTX in terms of radiographic progression, implying that IGU may be considered as an initial therapeutic option for patients with active RA. Trial Registration:. https://classic.clinicaltrials.gov/, NCT01548001.